SPAIN IN THE EUROPEAN UNION: CHALLENGES AND OPPORTUNITIES (Academicia Globe: Inderscience Research, 2024)
Spain’s membership in the European Union represents a complex tapestry of triumphs and tribulations. As a cornerstone of the EU project, Spain’s role extends far beyond its borders, shaping policies, fostering collaboration, and confronting shared challenges. However, amidst the backdrop of economic uncertainty, political upheaval, and societal transformation, Spain finds itself at a pivotal juncture, grappling with a myriad of challenges while endeavoring to harness the vast array of opportunities that lie ahead.